Transcutaneous Electrical Nerve Stimulation (TENS) Alleviates Brain Ischemic Injury by Regulating Neuronal Oxidative Stress, Pyroptosis, and Mitophagy - Zixuan Tan; Fang Dong; Linyu Wu; Yashuo Feng; Min Zhang; Feng Zhang (Hindawi Limited, 2023)
Background. As a noninvasive treatment, transcutaneous electrical nerve stimulation (TENS) has been utilized to treat various diseases in clinic. However, whether TENS can be an effective intervention in the acute stage of ischemic stroke still remains unclear. In the present study, we aimed to explore whether TENS could alleviate brain infarct volume, reduce oxidative stress and neuronal pyroptosis, and activate mitophagy following ischemic stroke. Methods. TENS was performed at 24 h after middle cerebral artery occlusion/reperfusion (MCAO/R) in rats for 3 consecutive days. Neurological scores, the volume of infarction, and the activity of SOD, MDA, GSH, and GSH-px were measured. Moreover, western blot was performed to detect the related protein expression, including Bcl-2, Bax, TXNIP, GSDMD, caspase-1, NLRP3, BRCC3, HIF-1α, BNIP3, LC3, and P62. Real-time PCR was performed to detect NLRP3 expression. Immunofluorescence was performed to detect the levels of LC3. Results. There was no significant difference of neurological deficit scores between the MCAO group and the TENS group at 2 h after MCAO/R operation (P>0.05), while the neurological deficit scores of TENS group significantly decreased in comparison with MCAO group at 72 h following MACO/R injury (P<0.05). Similarly, TENS treatment significantly reduced the brain infarct volume compared with the MCAO group (P<0.05). Moreover, TENS decreased the expression of Bax, TXNIP, GSDMD, caspase-1, BRCC3, NLRP3, and P62 and the activity of MDA as well as increasing the level of Bcl-2, HIF-1α, BNIP3, and LC3 and the activity of SOD, GSH, and GSH-px (P<0.05). Conclusions. In conclusion, our results indicated that TENS alleviated brain damage following ischemic stroke via inhibiting neuronal oxidative stress and pyroptosis and activating mitophagy, possibly via the regulation of TXNIP, BRCC3/NLRP3, and HIF-1α/BNIP3 pathways.